Pax, journey home - Pennypacker, Sara, 1951- (Pennypacker, Sara 1951 Pax, 2021)
It has been a year since newly orphaned Peter and his pet fox Pax, now a protective father, have seen each other, but their paths cross again when Pax's kit falls desperately ill forcing him to turn to the one human he knows he can trust.